Progesterone Prevents Traumatic Brain Injury-Induced Intestinal Nuclear Factor kappa B Activation and Proinflammatory Cytokines Expression in Male Rats - Gang Chen; Jinxin Shi; Yasuo Ding; Hongxia Yin; Chunhua Hang (Hindawi Limited, 2007)
We have previously shown that traumatic brain injury (TBI) can induce an upregulation of nuclear factor kappa B (NF-κB) and proinflammatory cytokines in the gut, which play an important role in the pathogenesis of acute gut mucosal injury mediated by inflammation. In this work, we investigated whether progesterone administration modulated intestinal NF-κB activity and proinflammatory cytokines expression after TBI in male rats. As a result, we found that administration of progesterone following TBI could decrease NF-κB binding activity, NF-κB p65 protein expression, and concentrations of interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) in the gut. TBI-induced damages of gut structure were ameliorated after progesterone injections. The results of the present study suggest that the therapeutic benefit of post-TBI progesterone injections might be due to its inhibitory effects on intestinal NF-κB activation and proinflammatory cytokines expression.